2022
DOI: 10.1038/s41392-022-00924-0
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of aggressive B-cell lymphoma with TP53 alterations administered with CAR T-cell cocktail alone or in combination with ASCT

Abstract: TP53 gene alteration confers inferior prognosis in refractory/relapse aggressive B-cell non-Hodgkin lymphoma (r/r B-NHL). From September 2016 to September 2020, 257 r/r B-NHL patients were assessed for eligibility for two trials in our center, assessing anti-CD19 and anti-CD22 chimeric antigen receptor (CAR19/22) T-cell cocktail treatment alone or in combination with autologous stem cell transplantation (ASCT). TP53 alterations were screened in 123 enrolled patients and confirmed in 60. CAR19/22 T-cell adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 62 publications
0
30
0
Order By: Relevance
“…In a retrospective study, in R/R DLBCL patients not treated with CAR-T cells, TP53 mutation was an independent inferior prognostic factor for OS, but in the CAR-T cell group, this significance could not be shown ( 31 ). CAR19/22 T-cell therapy combined with ASCT is efficacious in r/r aggressive B-NHL with TP53 alterations, producing a best ORR and CRR of 92.9% and 82.1%, respectively ( 32 ). However, in another retrospective study, TP53 alterations (mutations and/or copy number alterations) were still associated with inferior CR and OS rates in R/R DLBCL treated with CD19-CAR-T treatment ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study, in R/R DLBCL patients not treated with CAR-T cells, TP53 mutation was an independent inferior prognostic factor for OS, but in the CAR-T cell group, this significance could not be shown ( 31 ). CAR19/22 T-cell therapy combined with ASCT is efficacious in r/r aggressive B-NHL with TP53 alterations, producing a best ORR and CRR of 92.9% and 82.1%, respectively ( 32 ). However, in another retrospective study, TP53 alterations (mutations and/or copy number alterations) were still associated with inferior CR and OS rates in R/R DLBCL treated with CD19-CAR-T treatment ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…The feasibility of CAR T cell therapy shortly following high-dose chemotherapy and ASCT (HDT-ASCT) has been confirmed in several clinical studies (Table 2). Wei et al compared CAR T cell infusion after ASCT and CAR T cells alone and demonstrated that the best ORR, CR rate and long-term outcomes improved significantly in the combination group (62). In another study comparing CAR T cell infusion after ASCT and ASCT alone, the combination group showed higher CR rate (71% vs. 33%; p=0.003) and 3year PFS (80% vs. 44%; p=0.036) than the ASCT group, and demonstrated lower 3 year relapse/progression rate (15% vs. 56%; p=0.015) (63).…”
Section: Combination With Hsctmentioning
confidence: 99%
“…The most common combination scheme is cocktail infusion of CD19/CD22 CAR T cells in B cell malignancies (Figure 4) (62,192). Wang et al administered CD19 CAR T and CD22 CAR T cells at Day 0 and Day 2, respectively, to B-ALL and B-NHL patients.…”
Section: Combination With Different Car T Cell Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…After determining that a patient is suitable for CAR T-cell therapy, it is necessary to determine the lymphatic clearance scheme and dosing strategy according to the patient’s basic condition, to help the patient obtain the best blood environment and maximize the utilization of CAR T-cells [ 17 ]. Furthermore, for refractory and relapsed hematological malignancies, the combined application of multiple treatments may lead to longer event-free survival for patients [ 18 , 19 ]. The implementation of combined strategies to increase the persistence or antitumor activity of CAR T-cells has become a research hotspot.…”
Section: Introductionmentioning
confidence: 99%